Reclassification queries in a geographical data warehouse - Moreno, Francisco; Echeverri, Jaime; Arango, Fernando (Revista Técnica da Faculdade de Engenharia da de Zulia)
A data warehouse is a specialized database designed to support decision-making and is usually modeled using a multidimensional view of data. A multidimensional model includes dimensions that are composed of levels. The levels of a dimension are organized in a hierarchy, e.g., salespersons are grouped into stores. Throughout its lifespan a member (instance) of a level can be associated with several members of a higher level of the hierarchy, e.g., the salespersons can rotate between the stores. This succession of associations enables the formulation of queries such as: “How much did a salesperson sell in his n-th season (stay) in the store X?” In this paper, we enrich this type of query, known as season queries, with spatial features. This enhancement enables the formulation of queries such as: “How much did a salesperson sell in his n-th season in a given geographic region?” (A spatial query window that contains a set of stores.) In order to facilitate their formulation, we propose and incorporate an operator into a multidimensional query language to demonstrate their feasibility of implementation.